Cognitive dynamics of scientific curiosity - Subaşı, Ahmet. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The aim of this thesis is to develop an integrative perspective on the cognitive dynamics of scientific curiosity which influence and bias its motivational direction, i.e. its selectivity property. This perspective analyzes both individual dynamics and the outcomes of the interactions between these dynamics. In the thesis scientific curiosity is delimited as a particular type of specific epistemic curiosity and defined as an intrinsic motivation for systematically making sense of phenomena. It is argued that the compositional capacity of human mind, which finds its highest expression in language, makes possible the creation of meaning systems through which human mind systematically makes sense of phenomena. And the systematic aspect of making sense and its relationship to this compositional capacity is discussed. After elaborating on the definition of scientific curiosity, an inquiry is made into the emergence and processes of human symbolic capacity in order to reach findings as to the cognitive dynamics that influence the direction of scientific curiosity motivation. As the most basic definitional framework, compositional dynamic is defined as the creation of and activity within a dynamic system of meanings with a core and periphery the ultimate reference point of which is potentially everything. Other cognitive dynamics that function as subdynamics of this basic motivational dynamic are defined as interest dynamic, expansion dynamic, completion dynamic, hierarchical dynamic and perfection dynamic. The thesis aims to make the following four contributions to the literature: (1) Propose a comprehensive definition of the most basic dynamic of scientific curiosity which accounts for the diffuseness of children’s curiosity as well as the property of curiosity discussed under the title of ‘independence from interests’ in the philosophical literature; (2) hypothesize ‘hierarchical dynamic’ as a general selective tendency of scientific curiosity based on evidence from studies on children’s questions; (3) integrate the findings of the relevant theoretical perspectives under cognitive dynamics perspective that is offered in this thesis; and (4) analyze the interaction of individually studied dynamics and the nature of the research agenda this new perspective can offer.
Keywords: Curiosity.; Curiosity in children.